2017
DOI: 10.1098/rsos.170489
|View full text |Cite
|
Sign up to set email alerts
|

Social learning in otters

Abstract: The use of information provided by others to tackle life's challenges is widespread, but should not be employed indiscriminately if it is to be adaptive. Evidence is accumulating that animals are indeed selective and adopt ‘social learning strategies’. However, studies have generally focused on fish, bird and primate species. Here we extend research on social learning strategies to a taxonomic group that has been neglected until now: otters (subfamily Lutrinae). We collected social association data on captive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 51 publications
(72 reference statements)
0
31
0
Order By: Relevance
“…Thus it may be that Mff are relatively uninterested in socially mediated information, and, as a result, are also less likely to individually or socially learn the behaviour (overall low levels of attention to social demonstrations were also found in marmosets; a study on the attention of marmosets to knowledgeable demonstrators manipulating a problem-solving task found that individuals only attended to the demonstrator for a median of six seconds [ 58 ]). Indeed, a recent study on two different subspecies of otters also found differences between the subspecies in their levels of attention to socially mediated information [ 59 ]. However, this study did not directly test the role of genetics in pound-hammering in Mfa , and in the absence of data on the levels of attention to social information by wild Mfa , it is currently impossible to assess whether a distinct difference in the levels of individual and social learning does indeed exist between the subspecies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus it may be that Mff are relatively uninterested in socially mediated information, and, as a result, are also less likely to individually or socially learn the behaviour (overall low levels of attention to social demonstrations were also found in marmosets; a study on the attention of marmosets to knowledgeable demonstrators manipulating a problem-solving task found that individuals only attended to the demonstrator for a median of six seconds [ 58 ]). Indeed, a recent study on two different subspecies of otters also found differences between the subspecies in their levels of attention to socially mediated information [ 59 ]. However, this study did not directly test the role of genetics in pound-hammering in Mfa , and in the absence of data on the levels of attention to social information by wild Mfa , it is currently impossible to assess whether a distinct difference in the levels of individual and social learning does indeed exist between the subspecies.…”
Section: Discussionmentioning
confidence: 99%
“…We record the exact time of each manipulation and the identity of observers allowing us to have fine-grained observation data to construct a dynamic observation network, and to quantify the "per observation" social effect between different classes of individual. While association networks 6,[35][36][37] , genetic networks 8 , and static observation networks 11 have been used so far in modeling social transmission, very few studies used a dynamic observation network 7,28 . We aim here to challenge the notion of a single best strategy or a strategy associating several biases while previous studies on vervet monkeys reported a "copy adult females" strategy [23][24][25] .…”
mentioning
confidence: 99%
“…Our experimental manipulation of food type also did not appear to affect begging or sharing frequencies, which might be due the fact that most otter species are generalists (Timm- Davis et al 2015), and their diets reflect the local abundance of food (Almeida et al 2012;Clavero et al 2003;Krpo-Ćetković et al 2019;Lanszki and Körmendi 1996). Asian smallclawed otters are manual predators who rely on extractive foraging, using their clawless fingers to reach into crevices and sieve through silt (Ladds et al 2017). Their jaws are well equipped to crack hard shells compared to other mouth-oriented species and their partially webbed paws allow for greater dexterity (Sivasothi and Nor 1994;Timm-Davis et al 2015).…”
Section: Begging Behaviour and Food Type/abundance Treatmentsmentioning
confidence: 81%